Эволюция зубной и костной системы у представителей рода Sus - Хохлов, А.М. (Фактори експериментальної еволюції організмів, 2014)
Aims. Questions about phylogenetic development of tooth system in Sus gender representatives and also osteogenesis and processes in ontogenesis of wild European boar and domesticated breed of White Swine haven’t been enough covered in scientific sources. Methods. Morphological, zootechnical and histological methods of investigation of separate skeletal bones formation in ontogenesis of wild boar and White Swine breed have been used. Results. Weight of bone and osteogenesis in foetus of wild European boar in comparison with foetus development of White Swine breed has been studied. There was boar’s leg weight during 50-days age more on 118 %, than White Swine’s one. Bones of domestic animals grew more intensively at 70-days age that is connected with domestication process. However, development of red marrow and erithropoesis took place more intensively in bony tissue of wild animals. Conclusions. Premolars and incisors of Sus gender have been the most changed during evolutional processes of tooth system. Formation of bone and muscle system in ontogenesis process of wild and domestic swine proved that there was high intensity of osteogenesis for domestic animals, and there was high intensity of erithropoesis for wild swine. Wild boar can be donor of valuable peculiarities for high natural resistance and life of modern breeds.